Study of the new CSAR62 positive tone electron-beam resist at 40 keV electron energy. (March 2016) - Andok, R; Bencurova, A; Vutova, K; Koleva, E; Nemec, P; Hrkut, P; Kostic, I; Mladenov, G
Abstract: One of the few "top-down" methods for nano-device fabrication is the electron-beam lithography, which allows flexible patterning of various structures with a nanoscale resolution down to less than 10 nm. Thinner, more etching durable, and more sensitive e-beam resists are required for the better control, linearity, and uniformity of critical dimensions of structures for nano-device fabrication. Within the last decade, researchers have made significant efforts to improve the resolution of the nanoscale e-beam lithography. The resist material properties are an important factor governing the resolution. Only the e-beam resist ZEP 520 of the Japanese manufacturer ZEON is characterized by relatively good properties and thus meets most users' expectations. This paper deals with the investigation and simulation of the characteristics of the new less-expensive AR-P 6200 (CSAR 62) positive e-beam resist (available since May 2013, manufactured by Allresist GmbH company).